On the prediction of martensite formation in metals. (September 2017) - Galindo-Nava, E.I.
Abstract: A new approach to predict athermal martensite formation in metals is presented. It is based on computing the driving force of the transformation including a strain energy term induced by atomic shear displacements and energy terms due to substitutional and interstitial lattice distortions. The model is applied to prescribe the martensite and austenite start temperatures in Fe-, Ti- and Co-based alloys with no adjustable parameters. Expressions for M s variations with composition are derived for multicomponent systems. The transformation temperature hysteresis is predicted in Co alloys showing that this approximation can be used to design alloys with the shape memory effect. Graphical Abstract: